Development Of E-Modules with A Problem Based Learning Approach In Economic Learning - Reda Prasetya; Rusdarti Rusdarti; Dorojatun Prihandono (International Conference on Science, Education, and Technology, 2021)
The purpose of this research is how to develop an e-module with the Kvisoft Flipbook Maker application that is valid for use in economics learning. The design of this research is Research and Development (R&D). The research development design was adapted from the development of the Thiagarajan model which is better known as the 4-D model, define, design, develop, and disseminate. The results of the validation carried out by expert lecturers on e-modules with the Kvisoft Flipbook Maker application obtained an overall aspect score of 3.82. It can be said that the entire module received an assessment with very decent criteria. Data validation carried out by economics teachers on e-modules with the Kvisoft Flipbook Maker application obtained an overall aspect score of 3.93. It can be stated that all modules received an assessment with very decent criteria, based on the total aspect of the score validation results for lecturers and teachers in the e-module got a score of 3.87 with this e-module validation getting a very decent category score.